Chronobiological peculiarities of psychic disorders course at the example of metabolic syndrome patients - Ts. B. Abdriachimova; K. I. Kleban; D. P. Sapon (Kazimierz Wielki University, 2017)
Desynchronosis presenting in patients with metabolic syndrome significantly affects the underlying metabolism, eating behavior, mental and physical activity. On on example of a clinical case, patients with a depressive episode of moderate severity and  clinically confirmed metabolic syndrome on the treatment achieved a significant improvement on their mental status and reduced manifestations on metabolic disorders. The study on chronobiological features on the course on mental disorders on combination with metabolic syndrome is a promising direction on medical practice, which will improve the results on treatment on patients with a similar pathology.